If by x2 . y2 you mean ##x^2\cdot y^2##, then it is not equal to ##(x-y)(x+y)##.
It is true that ##x^2-y^2=(x-y)(x+y)##. It is also true that ##xy-y^2=(\sqrt{xy}-y)(\sqrt{xy}+y)## . Try substituting ##x=8## and ##y=2## to see how it works.
We Value Quality
• Topics based on mainstream science
• Proper English grammar and spelling We Value Civility
• Positive and compassionate attitudes
• Patience while debating We Value Productivity
• Disciplined to remain on-topic
• Recognition of own weaknesses
• Solo and co-op problem solving